Effect of low-lying rotational energy levels on fusion cross-section - Jain, Nishu (My University, 2020)
In this work, the effect of low-lying rotational energy levels are studied on the fusion cross-section for the 16O- and 40Ca-induced reactions at energy below and around the Coulomb-barrier using the CCFULL code. It is observed that major contribution to the fusion cross-sections comes from the 2+ and 4+ states. It is also investigated that up to how many states to be include in the channel coupling approach that will be good enough for the convergence of calculated fusion cross section towards experimental data. The fusion cross section is enhanced as compare to the single barrier penetration model. The impact of sign and magnitude of β-value and surface diffuseness is also studied on the fusion cross section. The theoretically calculated fusion cross-sections for 16O- and 40Ca-induced reactions are also compared with the corresponding experimental data.
Keywords: Fusion cross-section; channel coupling